لغة الجسد في مسرحيات الأطفال - صغيور نجاة -هبازي فضيلة (جامعة محمد بوضياف -المسيلة, 2024)
يعد التواصل الإنساني ظاهرة معقدة تتجاوز الكلمات المنطوقة لتشمل عالمًا غنيًا بالإشارات والإيماءات التي تعبر عن المعاني والمشاعر. من هنا تبرز أهمية لغة الجسد كنسق اتصالي رئيسي يعتمد عليه الإنسان في حياته اليومية، ويكتسي هذا الموضوع أهمية خاصة في مجال المسرح، حيث يتحول الجسد إلى أداة رئيسية للتعبير الفني والجمالي. في عالم المسرح، يصبح كل حركة، وكل إيماءة، وكل تعبير وجهي، جزءًا من لغة مرئية تهدف إلى إيصال قصة وإثارة العواطف ونقل الأفكار. لذا، يمثل فهم لغة الجسد في المسرح وسيلة حيوية لفهم أعمق للتواصل الإنساني. ينطلق هذا البحث من إشكالية رئيسية تتمحور حول دور لغة الجسد في المسرح وتطبيق المقاربات السيميائية على مسرحية صامتة حول "خطورة مواقع التواصل الاجتماعي". يهدف البحث إلى فهم العلاقة بين الجسد والتواصل الإنساني من خلال تحليل كيف يستخدم الإنسان لغة الجسد للتعبير عن المشاعر والانفعالات عوضًا عن اللغة اللفظية، وتسليط الضوء على أهمية حركة الجسد كمحور أساسي في تحليل لغة الجسد، مع التركيز على الإيماءة كخطاب بصري دلالي. يهدف البحث إلى تحقيق مجموعة من الأهداف، من أبرزها: تأسيس نظرية شاملة لعلم لغة الجسد وخاصة الدلالات الجسدية التي تتفاعل مع النص المسرحي، واستكشاف الطرق التي يستخدمها الجسم للتواصل ونقل المعنى، وتصنيف معاني ودلالات الجسد حسب الوظيفة التي تؤديها في المسرح. تبرز أهمية الدراسة في كونها تساهم في تجديد مجال البحث العلمي من خلال التطرق لجانب تم إهماله في البحوث العلمية في الجزائر، وجمع وتنظيم المعرفة المتعلقة بلغة الجسد، وتقديم مقاربات جديدة في تحليل لغة الجسد، وتطبيق عملي على الأعمال المسرحية من خلال تحليل لغة الجسد للممثلين، وإثراء الحقل العلمي المتعلق بالاتصال ولغة الجسد. ويعتمد البحث على المقاربة السيميائية لتحليل لغة الجسد كنظام دلالي، مستخدمًا مقاربة راي بيردويستل لتقطيع الحركات الجسدية والإيماءات إلى وحدات حركية دالة. كما يستخدم البحث مخطط رومان جاكبسون للوظائف اللغوية لتحديد الوظائف التي تلعبها كل إيماءة. تتركز عينة الدراسة على مسرحية "صامتة حول خطورة مواقع التواصل الاجتماعي" التي قدمها المسرح الجزائري، وذلك لأهمية الموضوع الذي تتناوله وكونها مسرحية تعليمية تربوية مناسبة للتحليل السيميائي. كما يسعى هذا البحث إلى المساهمة في فهم أعمق للغة الجسد ودورها في المسرح، مع التركيز على تطبيق المقاربات السيميائية في تحليل العروض المسرحية. بهذا، يمكن أن نفتح آفاقًا جديدة لفهم وتفسير التواصل غير اللفظي، مما يعزز من قدرتنا على تفسير الأعمال الفنية بطرق أكثر عمقًا وإثراءً. الكلمات الافتتاحية : المسرح، الطفل، الإيماءات Abstract : Human communication is a complex phenomenon that goes beyond spoken words to include a world rich in signs and gestures that express meanings and feelings. Hence, the importance of body language as the main communication format that a person relies on in his daily life, and this topic is of particular importance in the field of theater, where the body turns into a major instrument of artistic and aesthetic expression. In the world of theater, every movement, every gesture, every facial expression, becomes part of a visual language aimed at conveying a story, evoking emotions and conveying thoughts. Understanding body language in theatre is therefore a vital means to a deeper understanding of human communication. This research proceeds from a major problem centered on the role of body language in theater and the application of semiotic approaches to a silent play about the "danger of social networking sites". The research aims to understand the relationship between the body and human communication by analyzing how humans use body language to express feelings and emotions instead of verbal language, and highlighting the importance of body movement as a key axis in body language analysis, focusing on gesture as a visual semantic speech. The research aims to achieve a set of goals, the most prominent of which are: establishing a comprehensive theory of the science of body language, especially bodily semantics that interact with the theatrical text, exploring the methods used by the body to communicate and convey meaning, and classifying the meanings and semantics of the body according to the function it performs in the theater. The importance of the study is highlighted in that it contributes to the renewal of the field of scientific research by addressing an aspect that has been neglected in scientific research in Algeria, collecting and organizing knowledge related to body language, providing new approaches in body language analysis, practical application to theatrical works through the analysis of the body language of actors, and enriching the scientific field related to communication and body language. The research is based on the semiotic approach of analyzing body language as a semantic system, using ray birdwhistle's approach to break down physical movements and gestures into functional motor units. The research also uses the Roman Jakobson scheme of linguistic functions to determine what functions each gesture plays. The sample of the study focuses on the play "silent about the danger of social networking sites" presented by the Algerian theater, due to the importance of the topic it deals with and being an educational educational play suitable for semiotic analysis. This research also seeks to contribute to a deeper understanding of body language and its role in theater, focusing on the application of semiotic approaches in the analysis of theatrical performances. With this, we can open new horizons for understanding and interpreting non-verbal communication, enhancing our ability to interpret works of art in more profound and enriching ways. key words: theater, child, gestures .